Optical properties of TiAISiN based thin films - Nakonechna, O.I.; Poperenko, L.V.; Yurgelevych, I.V. (Functional Materials, 2005)
Spectroellipsometric investigations of optical properties of TiAISiN based thin films have been performed. The dispersive dependences of the film optical conductivity о have been obtained in the 1-5 eV spectral range. The observed intense absorption in the near ultraviolet range and some low intensity peculiarities in the near infrared one against a background of intraband absorption in the о curves are related to the interband electron transitions. The character differences in о curves for various coatings could be explained by different chemical composition and the deposition techniques. Проведены спектроэллипсометрические исследования оптических свойств тонких пленок на основе TiAISiN. Получены дисперсионные зависимости оптической проводимости о покрытий в спектральном интервале 1—5 эВ. Интенсивное поглощение в ближней ультрафиолетовой спектральной области и малоинтенсивные особенности в ближней инфракрасной области на фоне внутризонного поглощения, которые наблюдаются на кривых о, связаны с междузонными переходами электронов. Отличия в характере кривых о для различных покрытий можно объяснить различными химическими составами, а также способами их напыления. Проведено спектроеліпсометричні дослідження оптичних властивостей тонких плівок на основі TiAISiN. Отримано дисперсійні залежності оптичної провідності ст покриттів у спектральному інтервалі 1—5 еВ. Інтенсивне поглинання у ближній ультрафіолетовій спектральній області та малоінтенсивні особливості у ближній інфрачервоній області на фоні внутрішньозонного поглинання, які спостерігаються на кривих ст, пов’язані з міжзонними переходами електронів. Відмінності у характері кривих ст для різних покриттів можна пояснити різними хімічними складами, а також способами їх напилення.